(untitled) (Літератури світу: поетика, ментальність і духовність, 2017)
In this article the attempt of the determination of the status of the novel series about the peculiar children by Ransom Riggs in the literary-art process of the beginning of the XXI century is realised for the first time. Accordingly our attention is concentrated on the questions of tradition and innovation decisions in this trilogy by comparison with its typological and / or genetic given art row. Also we analyse the way of function and the role of the national component in the named novel circle.